PELATIHAN PERSONAL BRANDING AND COMMUNICATION UNTUK MENINGKATKAN PERCAYA DIRI MAHASISWA SEMESTER AKHIR DI STAK ANAK BANGSA - Sukri, Urbanus; Sari, Evi Catur; Kailuhu, Christin Destalia (Jurnal PKM Setiadharma, 2023)
In the development of this increasingly fast and sophisticated world, many people compete to equip themselves with various skills, one of which is branding themselves and improving how to communicate effectively and efficiently or on target. Good communication can improve skills, influence the interlocutor and even increase self-confidence. The Community Service (PkM) method is descriptive qualitative with a literature study approach to strengthen this writing. The results obtained from personal branding and communication training for students at Sekolah Tinggi Agama Kristen Anak Bangsa are: Students respond as a whole that the importance of building personal branding and training communication from now on, in addition to increasing self-confidence the training is a provision for students to face community conditions/sites that later they become stakeholders so that student knowledge increases, which needs to be done 1) Students need to find out what abilities they have, 2) Ensure students want to be widely known as what, 3) Do it with everything consistently, which means keep training him.